Advanced Concepts for Intelligent Vision Systems 12th International Conference, ACIVS 2010, Sydney, Australia, December 13-16, 2010, Proceedings, Part I - Blanc-Talon, Jacques.; Bone, Don.; Philips, Wilfried.; Popescu, Dan.; Scheunders, Paul. (Lecture Notes in Computer Science,, 2010)
This book constitutes the refereed proceedings of the 12th International Conference on Advanced Concepts for Intelligent Vision Systems, ACIVS 2010, held in Changchun, China, in August 2010. The 78 revised full papers presented were carefully reviewed and selected from 144 submissions. The papers are organized in topical sections on image processing and analysis; segmentation and edge detection; 3D and depth; algorithms and optimizations; video processing; surveillance and camera networks; machine vision; remote sensing; and recognition, classification and tracking.